CDK4 phosphorylation status and rational use for combining CDK4/6 and BRAF/MEK inhibition in advanced thyroid carcinomas - Pita, Jaime M.; Raspé, Eric; Coulonval, Katia; Decaussin-Petrucci, Myriam; Tarabichi, Maxime; Dom, Geneviève; Libert, Frederick; Craciun, Ligia; Andry, Guy; Wicquart, Laurence; Leteurtre, Emmanuelle; Trésallet, Christophe; et al. (Frontiers in Endocrinology, 2023)
Background: CDK4/6 inhibitors (CDK4/6i) have been established as standard treatment against advanced Estrogen Receptor-positive breast cancers. These drugs are being tested against several cancers, including in combinations with other therapies. We identified the T172-phosphorylation of CDK4 as the step determining its activity, retinoblastoma protein (RB) inactivation, cell cycle commitment and sensitivity to CDK4/6i. Poorly differentiated (PDTC) and anaplastic (ATC) thyroid carcinomas, the latter considered one of the most lethal human malignancies, represent major clinical challenges. Several molecular evidence suggest that CDK4/6i could be considered for treating these advanced thyroid cancers. Methods: We analyzed by two-dimensional gel electrophoresis the CDK4 modification profile and the presence of T172-phosphorylated CDK4 in a collection of 98 fresh-frozen tissues and in 21 cell lines. A sub-cohort of samples was characterized by RNA sequencing and immunohistochemistry. Sensitivity to CDK4/6i (palbociclib and abemaciclib) was assessed by BrdU incorporation/viability assays. Treatment of cell lines with CDK4/6i and combination with BRAF/MEK inhibitors (dabrafenib/trametinib) was comprehensively evaluated by western blot, characterization of immunoprecipitated CDK4 and CDK2 complexes and clonogenic assays. Results: CDK4 phosphorylation was detected in all well-differentiated thyroid carcinomas (n=29), 19/20 PDTC, 16/23 ATC and 18/21 thyroid cancer cell lines, including 11 ATC-derived ones. Tumors and cell lines without phosphorylated CDK4 presented very high p16CDKN2A levels, which were associated with proliferative activity. Absence of CDK4 phosphorylation in cell lines was associated with CDK4/6i insensitivity. RB1 defects (the primary cause of intrinsic CDK4/6i resistance) were not found in 5/7 tumors without detectable phosphorylated CDK4. A previously developed 11-gene expression signature identified the likely unresponsive tumors, lacking CDK4 phosphorylation. In cell lines, palbociclib synergized with dabrafenib/trametinib by completely and permanently arresting proliferation. These combinations prevented resistance mechanisms induced by palbociclib, most notably Cyclin E1-CDK2 activation and a paradoxical stabilization of phosphorylated CDK4 complexes. Conclusion: Our study supports further clinical evaluation of CDK4/6i and their combination with anti-BRAF/MEK therapies as a novel effective treatment against advanced thyroid tumors. Moreover, the complementary use of our 11 genes predictor with p16/KI67 evaluation could represent a prompt tool for recognizing the intrinsically CDK4/6i insensitive patients, who are potentially better candidates to immediate chemotherapy.